Associations of Alcohol, Marijuana, and Polysubstance use with Non-Adherence to Covid-19 Public Health Guidelines in a us Sample. Issue 2 (April 2021) - Fendrich, Michael; Becker, Jessica; Park, Crystal; Russell, Beth; Finkelstein-Fox, Lucy; Hutchison, Morica
Background: We sought to understand the association between heavy alcohol and frequent drug use and non-adherence to recommended social distancing and personal hygiene guidelines for preventing the spread of COVID-19 early in the US pandemic. Methods: A survey was offered on the crowdsourcing platform, Amazon Mechanical Turk (MTurk) during April 2020 (the early days of strict, social distancing restrictions). The study included 1, 521 adults ages 18 years and older who resided in the US and were enrolled as MTurk workers, i.e., workers who are qualified by Amazon to complete a range of human interaction tasks, including surveys through the MTurk worker platform. Main predictors included measures of heavy drinking, marijuana, and polysubstance use. The dependent measures were measures of social distancing and personal hygiene, based on guidelines recommended at the time of the survey by the US Centers for Disease Control to prevent the spread of COVID-19. Results: We found consistent negative associations between heavy drinking and drug use and adherence to social distancing and personal hygiene. Additionally, three control variables, age, gender, and race/ethnicity, were significant correlates of adherence to these measures. Conclusions: The findings here are consistent with previous research exploring links between substance use and other adverse health behaviors. Further, the negative association between heavy drinking (five or more drinks in one sitting) and adherence underscore the public health risks entailed with the unrestricted reopening of public drinking establishments.